Field-induced slow magnetic relaxation in pseudooctahedral cobalt(ii) complexes with positive axial and large rhombic anisotropy. Issue 4 (9th January 2019) - Świtlicka, Anna; Palion-Gazda, Joanna; Machura, Barbara; Cano, Joan; Lloret, Francesc; Julve, Miguel
Abstract : The preparation, X-ray crystal structure, spectroscopic and variable-temperature dc and ac magnetic properties of two six-coordinate cobalt(ii ) complexes of formula [Co(bim)4 (tcm)2 ] (1 ) and [Co(bmim)4 (tcm)2 ] (2 ) are reported. Abstract : The preparation, X-ray crystal structure, spectroscopic and variable-temperature dc and ac magnetic properties of two six-coordinate cobalt(ii ) complexes of formula [Co(bim)4 (tcm)2 ] (1 ) and [Co(bmim)4 (tcm)2 ] (2 ) (bim = 1-benzylimidazole, bmim = 1-benzyl-2-methylbenzimidazole and tcm − = tricyanomethanide ion) are reported.1 and2 crystallize in the monoclinic P 21 / n and C 2/ c space groups with the asymmetric units composed of one tcm − ion and half the [Co(bim)4 ] 2+ and [Co(bmim)4 ] 2+ complex cations, respectively. Their cobalt atoms are in compressed (1 )/rhombic (2 ) CoN6 octahedral environments, the axial positions being occupied by monodentate tricyanomethanide anions. The neutral molecules in1 are linked through weak C–H⋯N type interactions into supramolecular chains, which are further interconnected into supramolecular 2D motifs by C–H⋯π stacking. No short intermolecular interactions occur in2 . The values of the shortest intermolecular cobalt–cobalt separation are 10.901(1) (1 ) and 10.577(3) Å (2 ). Detailed ac and dc magnetic studies indicate that1 and2 are field-induced single-ion magnets (SIMs) with D = +46.1 (1 )/+80.1 cm −1 (2 ) thus presenting new examples of SIMs with transversal magnetic anisotropy. Theoretical calculations by CASSCF/NEVPT2 support these results and suggest that the relaxation of the magnetization occurs in the ground state under applied fields through two Orbach processes possibly bound to low-lying vibrational modes. Q-band EPR study for polycrystalline samples1 and2 at low temperatures confirms the positive sign of D, allows the rough estimation of the E / D ratio [0.144 (1 ) and 0.180 (2 )] and reveals the occurrence of a strong asymmetry in the g -tensors. The values found for the spin-reversal barrier, E a ≈ 28 and 11 cm −1 (1 ) and 20 and 9 cm −1 (2 ), are within the range of those found in other cobalt(ii ) field-induced SIMs with a pseudooctahedral trans -CoN4 N′2 chromophore.